2020
DOI: 10.1002/jper.20-0519
|View full text |Cite
|
Sign up to set email alerts
|

Peri‐implant marginal mucosa defects: Classification and clinical management

Abstract: Peri-implant marginal mucosa defects (PMMDs) are alterations of the periimplant soft tissue architecture characterized by an apical discrepancy of the mucosal margin respective to its ideal position with or without exposure of transmucosal prosthetic components or the implant fixture surface. PMMDs may not only represent an esthetic concern but also predispose to biofilm accumulation and subsequent initiation and progression of peri-implant inflammatory diseases. A treatment-driven classification for tooth-bou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 34 publications
0
22
0
4
Order By: Relevance
“…In our study, participants responded similarly that loss of the interdental papilla, gingival recession, exposure of the implant margin and a poor emergence profile are the most common aesthetic complications associated with dental implants. Recent studies in the literature have reported aesthetic complications, revealing that between 4 and 16% of single implant crowns in the anterior maxilla fail for aesthetic reasons [48][49][50]. The most common aesthetic complication is gingival recession exposing the implant/abutment junction, with one study reporting up to 61% of cases with at least 1 mm of gingival recession on the facial aspect.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, participants responded similarly that loss of the interdental papilla, gingival recession, exposure of the implant margin and a poor emergence profile are the most common aesthetic complications associated with dental implants. Recent studies in the literature have reported aesthetic complications, revealing that between 4 and 16% of single implant crowns in the anterior maxilla fail for aesthetic reasons [48][49][50]. The most common aesthetic complication is gingival recession exposing the implant/abutment junction, with one study reporting up to 61% of cases with at least 1 mm of gingival recession on the facial aspect.…”
Section: Discussionmentioning
confidence: 99%
“…These deformities have been defined as alterations of the peri-implant soft tissue morphology characterized by an apical discrepancy of the mucosal margin respective to its ideal position with or without exposure of transmucosal prosthetic components or the implant fixture surface. 73 On the other hand, gingival recession defects (GRDs) are defined periodontal deformities characterized by an apical migration of the gingival margin respective to the cementoenamel junction (CEJ) resulting in partial exposure of the root surface to the oral cavity, which may have important esthetic, functional, and periodontal health implications. 74 In the natural dentition, GRDs are assessed by determining the relative position of the gingival margin respective to the cementoenamel junction (CEJ).…”
Section: Peri-implant Soft Tissue Dehiscencesmentioning
confidence: 99%
“…Proper management of these defects can be very challenging and may require a purely surgical 77,78 or, in most situations, a combined multidisciplinary approach, including surgical, prosthetic, and even orthodontic therapy. 73,79 7 | FINAL REMARKS…”
Section: Peri-implant Soft Tissue Dehiscencesmentioning
confidence: 99%
See 2 more Smart Citations